Konsekuensi Biologis Pemanasan Global dengan Penekanan Terhadap Interaksi Serangga-Tumbuhan - Shahabuddin Shahabuddin (Biocelebes, 2009)
Global warming that caused by increasing of C02 in atmosphere effects many aspect on organism lives, including insects-plants interactions. The effect of CO2 increased will more complex when interact with another environment factors such as Nitrogen increased and atmosphere temperature increased. Global warming effects on physiology, phenology, distribution, adaptation, and interaction among species. Increasing of C02 gases in atmosphere potentially to rise attack of herbivory insects and effects on their natural enemy. Eventhough, the effect is very species spesific  and specific system on insects-plants interactions. It is needed  holistic understanding to build the strategy for herbivory insects controlled. In the other side, C02 increasing is a ecological issue that caused and effects to human life. It is need proactive attitude and communication to handle this problem together.